Obesity Associated Reproductive and Sexual Syndrome(OARS) in Men - Sanjay Kalra; Atul Dhingra; Nitin Kapoor (Journal of the Pakistan Medical Association, 2024)
Obesity, which has emerged as a major global public health challenge, is associated with myriad medical and multisystemic complications. Obesity impacts the male reproductive and sexual function in multiple ways as well. However, perhaps because of the focus on cardiovascular and metabolic health, the gonadal aspects of obesity medicine have not been given due attention. We propose the term OARS to describe obesity-associated reproductive and sexual syndrome in men living with obesity. OARS can be defined as a constellation of functional, hormonal, and structural abnormalities that affect the reproductive and sexual health of such men. The term OARS should attract attention to this neglected field and prompt efforts to prevent and address the needs of men living with obesity. Keywords: hypogonadism, infertility, obesity, overweight, sexual dysfunction, sexuality, spermatogenesis, subfertility